Incidental collocation learning from reading-only, reading-while-listening, and reading aloud: The roles of input mode, test modality, and prior vocabulary knowledge - Vu, Duy Van; Peters, Elke (Studies in Second Language Learning and Teaching, 2025)
The present study examined incidental collocation learning from reading-only, reading-while-listening, reading aloud, and factors that affect learning (i.e., test modality, prior vocabulary knowledge, and type of collocation). One hundred Vietnamese learners of English as a foreign language (EFL) with pre-intermediate level of English proficiency were assigned to an experimental group and a control group. During three weeks, the participants in the experimental group read three texts embedded with 20 target verb-noun and adjective-noun collocations in three different reading modes in a counterbalanced fashion: reading-only, reading-while-listening, and reading aloud. Learning gains were measured at form recall level in a pretest and a delayed posttest using both written and oral test items that were also counterbalanced. The findings revealed that reading mode had a significant effect on incidental collocation learning. Both reading-while-listening and reading aloud led to more learning gains than reading-only. Test modality did not have a significant effect on the results. In addition, learners’ prior vocabulary knowledge significantly predicted the learning gains.